Design of a human body channel communication transceiver using convolutional codes. (June 2020) - Chung, Ching-Che; Sheng, Duo; Li, Ming-Hsuan
Abstract: This paper presents a wideband signaling body channel communication (BCC) transceiver that uses the convolutional encoding method. The proposed transmitter uses the convolutional encoding method to increase the data reliability, and the modulated data are transmitted directly to a human body through a SMA cable and an electrode. In the receiver side, the oversampling phase detection clock and data recovery circuit with convolutional encoding method recovers the clock and data and increases 1.8x random data jitter tolerance (i.e., 50ns–90ns) at 10 −9 BER. The proposed BCC transceiver, except for the pre-amplifier of the RX, can be realized as a synthesizable digital IP. Thus, the proposed design can be ported to different processes in a short time. The feasibility of the proposed transceiver architecture was verified by the FPGA, and no bit errors occurred over 10 8 bits received at data rate 3.125 Mbps in transmission distance under 140 ​cm, which indicates the transceiver is very suitable for high-performance BCC applications.